1992
DOI: 10.1001/archderm.1992.01680150083011
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Proper Vehicle Selection in the Detection of Minoxidil Sensitivity

Abstract: Patch testing in cases of suspected minoxidil allergic contact dermatitis should include testing with minoxidil in propylene glycol. Omitting this testing may cause diagnoses and therapeutic formulation alternatives to go unrecognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Lotions, creams, and gels with sulfacetamide, ketoconazole (129), tar or ciclopirox (130) are available. Some gels contain fl ammable vehicles; patients should avoid fi re, fl ame, or smoking during and immediately after application (136). Thus, gel formulations may be especially effective for seborrheic dermatitis.…”
Section: Gels Lotions Creamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lotions, creams, and gels with sulfacetamide, ketoconazole (129), tar or ciclopirox (130) are available. Some gels contain fl ammable vehicles; patients should avoid fi re, fl ame, or smoking during and immediately after application (136). Thus, gel formulations may be especially effective for seborrheic dermatitis.…”
Section: Gels Lotions Creamsmentioning
confidence: 99%
“…As mentioned earlier, there are two available formulations of minoxidil, 2% and 5% solutions. However, there was no reaction seen to propylene glycol (20% aq) or 2 % minoxidil tested in alcohol or petrolatum (136). This may explain why phase III clinical trials showed that the 5% solution had three times more adverse reactions than the 2% solution (135).…”
Section: Minoxidilmentioning
confidence: 99%
“…Normal volunteers present some advantages when the patient population is likely to have been previously exposed. In the vehicle experiments reviewed here, we note with Merck Index primary literature review articles such as Chemical Abstracts calculations from Hansh-Leo data laboratory determination -the greater the affinity of a vehicle for the allergen it contains, the less the percutaneous absorption of the vehicle should occur -patch testing is done with occlusion which may alter delivery from 0 to 10 x -importance of stating which patch was used, because of penetration differences -vehicles may affect immunocompetent cells as well as altering penetration Clinical aspects -crucial to document clinical relevance with a use test, as it gives additional weight in the operational definition of allergic contact dermatitis intellectual frustration (including some of our own studies) that interpretation difficulty was compounded by inadequate numbers of controls for irritancy (e.g., (10,17)). Few studies had adequate irritant controls.…”
Section: Sample Sizementioning
confidence: 99%
“…Patch testing in cases with suspected minoxidil allergic contact dermatitis should include testing with minoxidil in propylene glycol because it has been found to be the allergen responsible in many cases 9 . In these patients an alternative solvent may be used 10 . Sensitization to the active ingredient minoxidil is extremely rare, but does exclude these patients from any further treatment containing minoxidil 9 …”
mentioning
confidence: 99%